Elemen Ateis Agnostik dalam Pemikiran Belia Islam di Negeri Selangor - Norsaleha Mohd Salleh; Hamidun Mohamad Hussin; Nurhanisah Senin; Phayilah Yama; Syarul Azman Shaharuddin; Abu Zaki Ismail; Mohd Khafidz Soroni; Khairatul Akmar Ab. Latif; Mustafa Kamal Amat Misra; Ahmad Shahir Masdan; Wan Fakhrul Razi Wan Mohamad (Majlis Agama Islam Selangor (MAIS), 2026)
Tier 4- Non-Indexed Publication